Impact of CMV Blips in Transplant Recipients. (4th October 2017) - Lodding, Isabelle Paula; Mocroft, Amanda; Bang, Caspar Da Cunha; Gustafsson, Finn; Iversen, Martin; Kirkby, Nikolai; Perch, Michael; Rasmussen, Allan; Sengeløv, Henrik; Sørensen, Søren Schwartz; Lundgren, Jens
Abstract: Background: Management of CMV infection in solid organ transplantation (SOT) and haematopoietic stem cell transplantation (HSCT) recipients mainly relies on screening of emerging CMV DNA in plasma or whole blood by PCR. However, a first positive CMV PCR may not be reproducible, but constitute a CMV blip (single positive CMV PCR measurements). Such blips are known from monitoring of other viral infections using PCR technology, and may either constitute a false positive read due to assay variability or reflect transient low-level viral replication. We investigated the impact of CMV blips in a cohort of SOT and HSCT recipients. Methods: SOT and HSCT recipients transplanted between 2010 and 2015, who had a known donor (D)/recipient (R) CMV IgG serostatus (D+/R+, D+/R- or D-/R+), and with ≥3 CMV PCRs fulfilling the CMV PCR triplicate criteria (Figure 1) were included ( N = 851). Odds ratio (OR) for factors associated with a triplicate being a blip was estimated by binomial regression adjusted for repeated measurements. Whether blips affected the hazard ratio (HR) for subsequent CMV infection was determined with a Cox model. Results: 851 transplant recipients generated 3883 CMV PCR triplicates (104 blips, 307 infections, 3472 negatives, Figure 1). In the 411 positive triplicates, the OR of a triplicate being a blip decreased with increasing CMV viral load of the second measurement ([vs. = 273 IU/mL]; >273–910 IU/mL: OR 0.2 [95% CI 0.1–0.4], >910 IU/mL: OR 0.07 [95% CI 0.03–0.2], P < 0.0001) and was elevated in recipients with intermediary/low-risk CMV IgG serostatus ([vs. those with high] OR 2.2 [95% CI 1.3–3.6] P = 0.003). If the cumulative exposure to viremia in the CMV blips was >910 IU/mL, there was a higher risk of subsequent CMV infection (HR 4.6 [95% CI 1.2–17.2] P = 0.02) (Figure 2). Conclusion: CMV blips are frequent while screening transplant recipients with CMV PCR. CMV blips >910 IU/mL is a risk factor for subsequent infection, indicating that CMV blips at least partly reflect transient low-level CMV infection in transplant recipients. These observations suggest that first positive CMV PCR results should be confirmed before initiation of anti-CMV treatment, especially if the viral load of the first positive PCR is <910 IU/mL, or if the patient has intermediary/low-risk serostatus. Disclosures: All authors: No reported disclosures.